Chevron, State Farm, and the Impact of Judicial Doctrine on Bureaucratic Policymaking. Issue 3 (30th September 2022) - Wiseman, Alan E.; Wright, John R.
Abstract : We explain how two landmark Supreme Court cases, Motor Vehicles Manufacturers Association of the U.S. v. State Farm Mutual Automobile Insurance Co. (1983) and Chevron U.S.A., Inc., v. Natural Resources Defense Council, Inc. (1984), have constrained congressional and presidential control of the bureaucracy. We provide an overview of these cases, and we note how the dominant theories of bureaucratic policy making in the political science literature fail to account for judicial doctrine in a meaningful way. We illustrate the implications of these cases for recent debates regarding regulatory rollbacks in the Trump administration, and we argue that bureaucratic control over the past forty years has tilted in favor of the judicial branch of American national government.